Pelatihan Terapi Komplementer Pijat Laktasi kepada Ibu Menyusui di Posyandu - Eva Santi; Linda Suryani; Dewinny Septalia Dale; Rika Sri Wahyuni; Iyang Maisi; Donny Hendra; Deby Yanthina; Asniati Asniati; Mustika Hana (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2022)
Breastfeeding is an unbeatable way of providing the ideal food for the healthy growth and development of the baby. In addition, it has a unique biological and psychiatric influence on the health of the mother and baby. Anti-infective substances contained in breast milk help protect the baby against diseases. However, breastfeeding is not always able to go on normally. Not a few mothers will complain such as breast swelling due to breast milk buildup due to uneven discharge or suction by the baby. Therefore, in order to avoid this kind of condition from occurring, it is necessary to do a lactation massage. The purpose of this community service is so that breastfeeding mothers know and understand how to overcome breast milk that does not come out during breastfeeding with lactation massage techniques so that the prevalence of babies who get exclusive breastfeeding is higher. This training was carried out at the Posyandu kejora Cemerlang Pekanbaru City with the number of participants as many as 20 people. The method of implementing activities broadly includes the stages of counseling, practice and evaluation. After providing education and practicing lactation massage, there was an increase in the knowledge and skills of pregnant women about lactation massage, where at the time of the pre-test the level of knowledge of mothers with the less category was 13 people (67%), while with the good category was 7 people (33%) while at the time of the post-test the level of knowledge of mothers with less category was 1 person (5%) and with a good category was 19 people (93%). It is necessary to carry out continuous mentoring activities for pregnant women which can be done through the formation of discussion groups either directly with regular meetings or indirectly with whatsapp groups, so that the problems experienced by mothers during pregnancy to breastfeeding can be resolved.